Photocleavable linker for the patterning of bioactive molecules - Wegner, Seraphine V.; Sentürk, Oya Ilke; Spatz, Joachim P. (Scientific reports, 2015)
Herein, we report the use of a versatile photocleavable nitrobenzyl linker to micropattern a wide variety of bioactive molecules and photorelease them on demand. On one end, the linker has an NHS group that can be coupled with any amine, such as peptides, proteins or amine-linkers and on the other end an alkyne for convenient attachment to materials with an azide functional group. This linker was conjugated with NTA-amine or the cell adhesion peptide cRGD to enable straightforward patterning of His6-tagged proteins or cells, respectively, on PEGylated glass surfaces. This approach provides a practical way to control the presentation of a wide variety of bioactive molecules with high spatial and temporal resolution. The extent of photocleavage can also be controlled to tune the biomolecule density and degree of cell attachment to the surface.